Everyone against us: public defenders and the making of American justice - Goodman, Allen (Chicago visions and revisions, 2023)
"In the American judicial system, even accused murderers, rapists, arsonists, and child abusers have voices and rights; and as the Miranda warning says, if they cannot afford a lawyer, one will be appointed to represent them. Enter the public defender, who must try to help people who have done reprehensible things-no matter their personal assessment of the client and situation. Former PD Allen Goodman draws upon a deep understanding of that milieu, conveying its complexities and dilemmas, reveling in great moral victories, enduring administrative inanity, and staggering from defeats. It is an intensely idealistic job, but also one that breeds corrosive cynicism. Goodman limns the difficulties of remaining a good human being while defending the worst of them"--